ECOLOGICAL AND ECONOMIC FOUNDATIONS OF EFFECTIVE CULTIVATION VEGETABLE CROPS - Y. Karpunina; E. Klimentova; A. Dubovitski (Вестник Северо-Кавказского федерального университета)
The article analyzes the dynamics of vegetable growing in The Russian Federation, identifies the main trends of changes in the industry. For a complex assessment ofvegetable crops cultivation the author's interpretation of determination of ecological and economic efficiency of vegetable production is offered. The study shows that the cultivation of vegetable crops, taking into account the actual intake of nutrients, often causes a negative balance of nutrients in the soil, that is, if there is a relative level ofprofitability of production, the ecological and economic eiciency of their use often has a negative value. This indicates the need not only for the joint application of organic and mineral fertilizers in optimal parameters, but also the search for alternative ways to ensure the reproduction of soil fertility, including using the principles of biologization and agroecology.